Analysis of Scout Extracurricular Activities on Student Discipline - Primadhani, Dewi Surya; Fajrin, Nilamsari Damayanti; Maulida (eductum: Jurnal Literasi Pendidikan, 2025)
This study aims to analyze the impact of scout extracurricular activities on student discipline. The research was conducted within a qualitative research framework, focusing on social phenomena that cannot be analyzed statistically. The methods used include observation, interviews, and documentation studies of student participation in scouting activities and their influence on disciplined behavior. The results show that participation in scouting activities significantly affects student discipline, particularly in terms of responsibility, time management, and adherence to rules. However, it was also found that some students still face challenges with attendance and proper use of uniforms, indicating the need for better management strategies to enhance student engagement. This study refers to literature that supports a positive correlation between scouting activities and student character development, especially in fostering discipline and moral values. The conclusions of this study are expected to provide insights for educators and school administrators to improve the effectiveness of scouting programs in schools, thereby contributing more effectively to the development of students' disciplined character.